Are structural funds a real solution for regional development in the European Union? A study on the Northeast Region of Romania - Ionel Bostan; Andrei-Alexandru Moroşan; Cristian Valentin Hapenciuc; Pavel Stanciu; Iulian Condratov (Journal of Risk and Financial Management, 2022)
Economic development has been a major priority for the European Commission, with significant amounts of Structural and Cohesion Funds being allocated in this direction. With the enlargements of the Union in 2004, 2007 and 2013, the Regional Development Policy faced a new challenge, with the disparity between new members and the community average being a notable one. The literature is divided with respect to the impact generated by funds allocated through the Regional Development Policy, as some authors claim the existence of positive effects, others identify conditional positive effects and other authors identify only negative effects and say that the whole support system needs to be rethought. This research presents an empirical approach to the issue of the effectiveness of the European Community's support system for business environments. An analysis is performed at the microeconomic level in order to quantify observable effects at the level of the SMEs that have benefited from non-reimbursable financial aid. The data obtained indicate that Structural and Cohesion Funds for business environments have a significant effect in the medium and long terms, contributing to the achievement of the general objective of the Regional Development Policy (reducing economic disparities between EU member states).
Keywords: 650; firms/SMEs; NEDR/Northeast Development Region of Romania; regional development; structural funds